Distinct Bacterial Microbiomes Associate with the Deep-Sea Coral Eguchipsammia fistula from the Red Sea and from Aquaria Settings - Röthig, Till; Roik, Anna; Yum, Lauren K.; Voolstra, Christian R. (Frontiers in Marine Science, 2017)
Microbial communities associated with deep-sea corals are beginning to be studied in earnest and the contribution of the microbiome to host organismal function remains to be investigated. In this regard, the ability of the microbiome to adjust to prevailing environmental conditions might provide clues to its functional importance. In this study, we characterized bacterial community composition associated with the deep-sea coral Eguchipsammia fistula under natural (in situ) and aquaria (ex situ) settings using 16S rRNA gene amplicon sequencing. We compared freshly collected Red Sea coral specimens with those reared for >1 year at conditions that partially differed from the natural environment, in particular regarding increased oxygen and food availability. We found substantial differences between the microbiomes associated with corals under each environmental setting. The core microbiome comprised only six bacterial taxa consistently present in all corals, whereas the majority of bacteria were exclusively associated either with freshly collected corals or corals from long-term reared aquaria settings. Putative functional profiling of microbial communities showed that corals in their natural habitat were enriched for processes indicative of a carbon- and nitrogen-limited environment in comparison to aquaria-reared corals, which might be reflective of differences in diet under in situ and ex situ conditions. The ability of E. fistula to harbor distinct microbiomes under different environmental settings might contribute to the flexibility and phenotypic plasticity of this cosmopolitan coral. Future efforts should further assess the role of these different bacteria in holobiont function, in particular since E. fistula is naturally present in markedly different environments.